Description of Mesopolobus askewi sp. nov. (Hymenoptera, Pteromalidae), with notes on the fauna of Asaphesinae and Pteromalidae (Hymenoptera, Chalcidoidea) collected from foliage of Picea abies (L.) H. Karst. in Bulgaria - Ivaylo Todorov; Mircea-Dan Mitroiu; Aneliya Bobeva; Peter Boyadzhiev (Biodiversity Data Journal, 2024)
Mesopolobus Westwood, 1833 consists of about 135 valid species worldwide. After the fundamental monograph of Graham (1969), 12 species have been described from continental Europe and three species have been described from the Canary Islands and Malta. Amongst them, one species, Mesopolobus blascoi Askew, 1994, has been synonymised under Mesopolobus maculipennis (Mercet, 1923). Only eight species have been reported from Bulgaria to date.Here we describe a new species, Mesopolobus askewi sp. nov. and present new data on the Bulgarian chalcidoid fauna obtained by sampling in foliage of the Norway spruce, P. abies. Mesopolobus askewi sp. nov. can be distinguished from the most morphologically similar species, M. longicollis Graham, by the following characters: clypeus with deeper emargination, fore wings with basal vein having complete row of setae, head blue to bluish-green, mesosoma bluish-green to green with coppery reflections, legs after coxae mostly fulvous, only distal one-fifth of meso- and metatibiae yellowish, protarsi with fifth segment yellowish, only tarsal claws fuscous, venation pale testaceous. Furthermore, we identified nine valid species of the family Pteromalidae belonging to four genera – Mesopolobus (three spp.), Pachyneuron (one sp.), Stenomalina (one sp.) and Trichomalus (four spp.) and one species of subfamily Asaphesinae (Chalcidoidea, incertae sedis), all represented in our samples by many specimens and none having previously been reported as associated with foliage of the Norway spruce. Three of the species are new records for the Bulgarian fauna.